2021
DOI: 10.25176/rfmh.v21i2.3615
|View full text |Cite
|
Sign up to set email alerts
|

Hand Hygiene Habit And Pathogens Found In Medical Students

Abstract: El objetivo fue conocer los hábitos de higiene de manos de los estudiantes de medicina; así como la población bacteriana residente en la palma de las manos. Se llevó a cabo un estudio observacional, descriptivo de tipo transversal, y se realizó una encuesta sobre la conducta de higiene de manos a 100 alumnos, y a otros 33 alumnos se les realizó cultivo microbiológico de la superficie palmar, el instrumento fue validado por juicio de expertos. En relación a los hábitos de higiene, el 74% mostró una actitud apro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…9%, and E. cloacae 9%. The study by Domínguez-Navarrete et al[ 26 ] revealed the presence of pathogenic bacteria on the hands of preclinical medicine students. A total of 60.6% of students were carriers of S. aureus, 3% Pseudomonas aeruginosa, 3% Enterobacter , and 18.1% Candida spp.…”
Section: Discussionmentioning
confidence: 99%
“…9%, and E. cloacae 9%. The study by Domínguez-Navarrete et al[ 26 ] revealed the presence of pathogenic bacteria on the hands of preclinical medicine students. A total of 60.6% of students were carriers of S. aureus, 3% Pseudomonas aeruginosa, 3% Enterobacter , and 18.1% Candida spp.…”
Section: Discussionmentioning
confidence: 99%